Répondre :
Réponse :
Il faut appliquer la double distributivité
A = (2x+ 3) ×(x + 6) = 2x*x+2x*6+3*x+3*6 = 2x²+12x+3x+18 =2x² +15x +18
B = (x - 6) × (5x + 1) = x*5x+x*1-6*5x-6*1 = 5x² +x-30x-6 = 5x²-29x-6
C=(7x-8)×(3-2x) = 7x*3-7x*2x -8*3+8*2x = 21x-14x²-24+16x =-14x²+37x -24
D=(8x-1)²
On utilise l'identité remarquable : (a-b)² = a²-2ab + b²
=(8x-1)²= (8x)²-2*(8x*1) +1² = 64x²-2*8x+1=64x² -16x+1
E=(5x-2)×(5x+2)
On utilise l'identité remarquable :( a+b)(a-b) = a²-b²
(5x-2)×(5x+2)=(5x)²-2² = 25x² -4
F= (-4 + x)(10 - 3x) = - 40+1 x+10x-3x² = -3x²+22x-40